Digoxin treatment and long-term mortality depending on left ventricular ejection fraction and atrial fibrillation: a propensity score matched analysis. (14th October 2021) - Grubler, M.R; Verheyen, N.D; Meinitzer, A; Fiedler, L; Tscharre, M; Roithinger, F.X; Tomaschitz, A; Pilz, S; Maerz, W
Abstract: Background/Introduction: Atrial fibrillation (AF) is a common heart rhythm disturbance, associated with an increased risk of stroke, hospital admissions and mortality, especially in patients with reduced ejection fraction. Among the oldest medications used for heart-rate control is digitalis, but largely due to observational studies showing an increased risk of death it has fallen out of favour. Recently newer clinical trials reported that the treatment with digitalis in permanent AF might be superior to beta blocker therapy in regard to functional status and symptom burden. Given this diverging results we attempt to analysis a large cohort of patients facilitating a propensity score matching algorithm. Purpose: To assess the associations of digitalis treatment with mortality in patients with increased cardiovascular risk. Methods: Patients were derived from a large cohort study including participants from a tertiary care centre who were referred to coronary angiography. The propensity score matching is based on a predefined list of variables, with digitalis as treatment. Matching strategy is nearest neighbour matching and to prove consistency, radius matching (radius = 0.1). For survival analysis we used a Cox proportional hazard regression comparing patients with and without digitalis for all-cause mortality. The analysis is conducted using STATA 13 MP. All patients provided written informed consent and the study was approved by the ethics committee. Results: A total of 2457 patients (median age: 63.5 [IQR = 56.3–70.6] years, 30.1% women) referred to coronary angiography, with a median follow up of 9.9 (IQR = 8.5–10.7) years were included. The matching process and the resulting propensity score fulfilled all statistical assumptions and resulted in a balanced cohort. The risk for all-cause mortality was higher among propensity score matched participants not treated with digitalis compared to patients on treatment (n=514) HR 3.03 (95% CI 2.5 to 3.7). Total mortality in patients with AF on digitalis after a median follow-up of 9.9 years was 27.6%. At baseline, only 42.4% of patients with AF were on oral anticoagulation. Conclusions: In the present cohort treatment with digitalis was associated with a lower risk of all-cause mortality after long-term follow-up. The patient population has a clinically significant 10-year mortality risk. The results may not apply to other cohorts but may help inform future clinical trials. Funding Acknowledgement: Type of funding sources: None.